Clomazone impact on fungal network complexity and stability - He, Hairong; Huang, Jiarui; Zhao, Zhenzhu; Feng, Weisheng; Zheng, Xiaoke; Du, Pengqiang (Frontiers in Microbiology, 2023)
Soil fungal network composition and stability is important for soil function, but there was less understanding about the impact of clomazone on network complexity and stability. In this work, two agricultural soils were used to investigate the impact of clomazone on fungal network complexity, composition, and stability. Two soils were treated with clomazone solution (0, 0.8, 8, and 80 mg kg–1) and kept in an incubator. Under the influence of clomazone, the fungal network node was decreased by 12-42; however, the average degree was increased by 0.169-1.468 and fungal network density was increased by 0.003-0.054. The keystone nodes were significantly changed after clomazone treated. Network composition was also impacted. Specifically, compared with control and clomazone treatments in both soils, the shared edges were less than 54 in all comparison, and network dissimilarity was 0.97-0.98. These results suggested that fungal network composition was significantly impacted. The network robustness was increased by 0.0018-0.0209 and vulnerability were decreased by 0.00018-0.00059 in two soils, which indicated that fungal network stability was increased by clomazone. In addition, the functions of the network communities were also changed in both soils. These results indicated that clomazone could significantly impact soil fungal network.